Analisis Pengaruh Locus of Control, Orientasi Tujuan, dan Self Efficacy Terhadap Berbagi Pengetahuan (Knowledge Sharing) Pada Tenaga Dosen Laboratorium Politeknik Ilmu Pelayaran (PIP) Makassar - Moh Aziz Rohman; Rudy Susanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Delays in implementing training and the number of lecturers being trained for new equipment is not commensurate with the number of classes being taught in the teaching and learning process, this requires a method of sharing knowledge (knowledge sharing). Sharing knowledge (knowledge sharing) is carried out when lecturers receive training on new equipment. It is hoped that this can be done both with colleagues and students. Several factors influence the success of knowledge sharing. Factors that influence knowledge sharing, a research model was developed using three independent variables which include locus of control, goal orientation, and self-efficacy. Data was obtained from 69 samples who were laboratory and simulator lecturers at the Makassar Maritime Science Polytechnic (PIP) which were then analyzed using the Multiple Regression Test. The results of Multiple Regression testing show that knowledge sharing is statistically influenced by locus of control, goal orientation, and self-efficacy, meaning that if locus of control, goal orientation, and self-efficacy increase, the practice of knowledge sharing will also increase.